Proactive marketing decision-making in digitalization age: How can data-based methodologies help to marketing research? - Pınarbaşı, Fatih (Springer Science and Business Media Deutschland GmbH, 2021)
The advancements in the marketplace and reactions of market actors are the key factors in the history of marketing research and decision-making. The various changes in the market environment play a crucial role in understanding and reacting to different marketing situations. From this perspective, the new data sources, contexts, and methodologies have been instrumental in understanding cases in the market environment and marketing-related concepts. Examining the marketplace and understanding the market cannot be sufficient for proactive marketing management, since the new marketplace requires a sophisticated approach evaluating the market actors and acting regarding the changing market variables. As the popularity of social media platforms and data-based technologies increase in the marketplace, the amount of produced data, the variety of data contexts, and the need to use new data-based methodologies increase. The “new” marketplace uses many social media and digital platforms daily and produces a large volume of data in different formats surrounding the customers and businesses in the marketplace. Digital platforms have begun to offer innovative data formats for internet users to express themselves as ephemeral media or multimedia formats, and these data formats as contexts require different data-based methodologies for understanding. The study seeks to examine the current data-based methodologies concept for marketing decision-making and marketing research. For this purpose, the study employs a review approach to evaluate the data-based methodologies for marketing research and decision-making context. The study evaluates the topic in three sub-sections: the big data, emerging data contexts and data-based methodologies. The comprehensive approach included in the study will contribute to a better understanding of current data-based methodologies and how can they be used for marketing decision-making.
Keywords: Digitalization Age; Proactive Marketing; Decision-Making; Marketing Research